THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION AND LOYALTY IN SUPERMARKET SECTORS - Ellen Tjandra, Jeane; Nurani, Nina; Faizun Mohamad Yazid, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study is focusing on the measurements of service quality towards customer satisfaction and customer loyalty in the context of supermarkets sectors in Indonesia. This study used quantitative method as such 500 questionnaires distributed, 341 responses were usable. The response rate is 68.2%. Questionnaire consist of 4 sections. Sections 1 is on the respondent’s profile and the rest is about the study topic. All together there are 35 questions including questions related to respondents’ profile. The survey used 5 Likert scales in which 1 is strongly disagree and 5 is strongly agree. 5 Likert scales was used to invite as accurate as possible responses from respondents. Data is analysed using structural equation model. The results of this research indicates that service quality is important towards the customer satisfaction and customer loyalty. The role of customer satisfaction between service quality and customer loyalty is also proven as significant. Business organizations related to the same industry must ensure that they focused on the service quality as it has been recognised as one of the step towards achieving customer loyalty.